Seasonality of Precipitation in TURKEY: Present and Future Assessments - Yasemin Ezber (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, the non-parametriccircular statistical method is used to analyze seasonality of precipitationover Turkey for past (1956-1975) and present (1986-2005) periods using bothstation data and gridded observation data (CRU-3.24). This method is alsoapplied to the CORDEX Europe domain for three different periods which coverearly century (2016-2035), mid-century (2046-2065) and end-century (2081-2099)to investigate the potential future changes in the seasonality under a pessimisticclimate scenario, CMIP5-RCP 8.5 (Coupled Model Intercomparison Project phase 5-RepresentativeConcentration Pathways 8.5). Seasonality Index (SI) overTurkey decreases from south (~0.6) to north (~0.1) for past and present periods.For the future periods, SI tends to increase in the south, especially in the south-easternAnatolian region, while it tends to decrease over the Black Sea and centralAnatolian regions. Beside SI, another outcome from the circular statistics is theaverage occurrence time of precipitation during a year. Winter months(December-January-February) are common occurrence time of precipitation ingeneral for past and present periods. Precipitation occurrence time for the futureperiods does not change much in the future periods for most of the regions exceptfor the central Black Sea and southeastern Anatolia where it shifts to Octoberand November, respectively.